2020
DOI: 10.1111/and.13786
|View full text |Cite
|
Sign up to set email alerts
|

Ginger juice prevents cisplatin‐induced oxidative stress, endocrine imbalance and NO/iNOS/NF‐κB signalling via modulating testicular redox‐inflammatory mechanism in rats

Abstract: Chemotherapy is a cornerstone option in cancer treatment owing to its efficacy and effect on quality of life of cancer patients. The action mechanism of anticancer agents is targeted at deregulating cell cycle machinery and inhibiting unscheduled proliferation of cancer cells (Lin et al., 2020). Unfortunately, chemotherapeutic anticancer drugs often exert deleterious effect on healthy cells and tissues leading to systemic toxicity (Negrette-Guzmán, 2019). The toxicity may become unbearable that the treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 53 publications
1
18
0
1
Order By: Relevance
“…When gonadotropin luteinizing hormone is released, it results in cAMP release and protein kinase A activation, which initiates a series of enzyme cascade reactions (Liu et al, 2015). In various studies examining the effects of CP on testicular and reproductive function, it has been shown that plasma or testicular total and free testosterone levels are also reduced; these results have often been associated with oxidative stress (Azab et al, 2020;Ceylan et al, 2020;Famurewa et al, 2020;Jourabi et al, 2020;Kohsaka et al, 2020;Majd et al, 2021;Saad et al, 2020;. In the present study, we also demonstrated that CPinduced oxidative stress significantly decreased total and free testosterone levels in rats' plasma.…”
Section: Discussionmentioning
confidence: 99%
“…When gonadotropin luteinizing hormone is released, it results in cAMP release and protein kinase A activation, which initiates a series of enzyme cascade reactions (Liu et al, 2015). In various studies examining the effects of CP on testicular and reproductive function, it has been shown that plasma or testicular total and free testosterone levels are also reduced; these results have often been associated with oxidative stress (Azab et al, 2020;Ceylan et al, 2020;Famurewa et al, 2020;Jourabi et al, 2020;Kohsaka et al, 2020;Majd et al, 2021;Saad et al, 2020;. In the present study, we also demonstrated that CPinduced oxidative stress significantly decreased total and free testosterone levels in rats' plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any notable action of LCP and CAPE on CP-induced increase in NO production might be related to the organ-specific action of 2 tested antioxidants, which has been reported for different natural compounds [18]. On the other hand, a decrease in NO production was found to be associated with an aggravation in CP-induced kidney damage [19], while an increase in its production and iNOS expression was associated with CP-induced peripheral neuropathy [20] and testicular tissue damage [21]. Thus, it might be difficult to predict what would be the most beneficial property of a drug/substance targeting the NO/iNOS mechanism in different organs affected by CP.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have also reported loss of body weight due to injection of CDDP. 26,27 We observed that the intake of food by the rats reduced as well as the water intake. Conceivably, reduced food consumption occasioned by the CDDP may contribute to the loss of weight as energy expenditure may be greater than energy harvested during the reduced food intake.…”
Section: Discussionmentioning
confidence: 88%